Beveridge Report (letter) - Rogers, Jack
1942-12-10 1942 1940s 2 pages N.F.S. Stn. 37. E. 1. Z. Brampton Road, Bexley Heath, Kent. December 10th. 1942. Dear Comrade, As a 'rank and file' member of the Fire Brigade Union, I would, on the eve of the consideration of the Beveridge report by the T.U.C., urge its complete rejection. Admittedly, it is a most advanced scheme, comprehensive in its scope and all-embracing in its benefits, and is a most meritorious effort, reflecting great credit upon Sir William Beveridge and his collaborators. I am convinced however, that it [is] the alternative of the Tory party to a Socialist Government and a planned economy. It does not provide for workers' control in industry, neither does its institution guarantee the abolition of labour exploitation. Further, it will not end the divisions of our class society, which is the mainspring of the capitalists, in their desire to continue the domination which their superiority in financial spheres enables them to wield. Only Socialist legislation can make such sweeping changes, and this fact is acknowledged by the Tories and the vast interests which they represent, by the presentation of this plan. It is a typical Tory move to secure class collaboration and to return to pre-war conditions make no mistake concerning the motive, comrade! I would not insult your intelligence by delving into the functions of the Trade Union movement, but I would like to mention what I consider to be a fundamental aim and a prime necessity today. That is, that Trade Unionism must recognise its function as a transitional stage in the establishment of a full and complete Socialist regime, and not merely be content with endeavouring to bring concessions from the employer class. It is no secret that capitalism is the very core, the heart of Nazism and Fascism, Surely, then, our immediate concern is that its destruction and downfall be hastened and worked for ; (which will not be achieved if we are satisfied to compromise!) let us hear no more of 'strategic withdrawals' In the sense of retreats from the capitalist class! It is now high time that we adopted an offensive spirit and began to contest every inch of the way, rather than adopt a submissive attitude in abandoning and renouncing the class struggle. The opposition must not be underrated. Trusts, Combines, Syndicates, and Industrialists make very formidable foes, and we are going to strengthen them considerably if we continue co-operation with them as hitherto. They will emerge from the war more strongly entrenched than ever, — to continue their struggle against us as a class. They have done it before, and will do the same things again if we are prepared to submit to their class domination. I would strongly urge you not to be deceived into believing that the class struggle is over or that it is an unimportant issue. The future hopes of the masses lie in the Socialisation of industry and commerce for the removal of such evils as the accumulation of wealth resultant upon private profiteering. By such measures alone can the emancipation of the workers be assured and their hopes and aspirations be fulfilled. Reformist and half measures are unsatisfactory and undesirable. 292/150.5/5/245